2001
DOI: 10.1084/jem.194.12.1875
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Receptor 7–dependent and –independent Pathways for Lymphocyte Homing

Abstract: Cognate interaction of chemokine receptor CCR7 on lymphocytes with its ligands CCL19 and CCL21 expressed on high endothelial venules (HEVs) is essential for effective migration of T and B cells across HEVs into secondary lymphoid organs. Plt mice, which lack expression of CCL19 and CCL21-ser, both ligands for CCR7 on HEVs, as well as CCR7-deficient mice, have a defective cell migration and reduced homing of lymphocytes. FTY720, a novel immunosuppressant, causes a reduction of lymphocytes in peripheral blood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 22 publications
5
93
0
Order By: Relevance
“…Mice lacking CCR7 show impaired ability to maintain tolerance to peripheral antigens as they develop signs of autoimmunity [70,71]: they exhibit lymphocyte infiltration in peripheral organs, elevated levels of circulating antibodies towards tissue-specific antigens, IgG deposition around the renal glomeruli, and increased susceptibility to inducible diabetes, and they can spontaneously develop chronic autoimmune renal disease [70]. These mice, as well as those lacking CCL19 and CCL21 (plt mice), which lack recognizable T cells zones within all LNs [72][73][74][75][76], can still mount strong cellular immune responses [6]. This is consistent with the mounting evidence that although B cell responses require their residence in functional lymph nodes, T cell immunity apparently does not, and T cells can be activated in the spleen or even liver when lymph nodes are absent or dysfunctional (reviewed in [77]).…”
Section: Lymphoid Organs In Peripheral Tolerancementioning
confidence: 99%
“…Mice lacking CCR7 show impaired ability to maintain tolerance to peripheral antigens as they develop signs of autoimmunity [70,71]: they exhibit lymphocyte infiltration in peripheral organs, elevated levels of circulating antibodies towards tissue-specific antigens, IgG deposition around the renal glomeruli, and increased susceptibility to inducible diabetes, and they can spontaneously develop chronic autoimmune renal disease [70]. These mice, as well as those lacking CCL19 and CCL21 (plt mice), which lack recognizable T cells zones within all LNs [72][73][74][75][76], can still mount strong cellular immune responses [6]. This is consistent with the mounting evidence that although B cell responses require their residence in functional lymph nodes, T cell immunity apparently does not, and T cells can be activated in the spleen or even liver when lymph nodes are absent or dysfunctional (reviewed in [77]).…”
Section: Lymphoid Organs In Peripheral Tolerancementioning
confidence: 99%
“…Previous reports demonstrated that S1P and FTY720 sensitize or enhance peripheral T cell migration to chemokines suggesting that sequestration of T cells within PLNs is dependent on both chemokine and S1PR engagement on the T cell surface (9,10,16 readily enter secondary lymphoid organs and migrate to appropriate T cell compartments. Conversely, in a variety of studies, a lack of chemokines or chemokine receptors prevents T cell trafficking and accumulation in the PLN, even if S1PR are stimulated (9,10,17). Our current results indicate that peripheral splenic T cells show enhanced migration to chemokines in the presence of S1PR stimulation, but can still migrate if S1P agonists are absent or if S1P 1 is desensitized or down-modulated.…”
Section: T Cell Entry Into Plnsmentioning
confidence: 45%
“…It is important to acknowledge that a limitation to our results is the use of vascular endothelial cells, because murine lymphatic endothelial cells and lines are not readily and reproducibly available, and with uncertainty as to whether those cells reliably reproduce the in vivo environment. Specific homophilic and heterophilic receptor interactions between leukocytes and endothelial cells result in both outside-in and inside-out signaling, initiating a complex process that results in transient dissolution and separation of endothelial adherens junctions to permit leukocyte transmural migration (17,18,27). The data here suggest that S1PR function is required for this step in T cell PLN egress.…”
Section: Endothelial Cell and Pln T Cell Interactionsmentioning
confidence: 58%
“…Chiba et al and Brinkmann et al reported that the precise mechanisms of PBL reduction by FTY720, at concentration orders of nanomoles per liter, have been considered to be accelerated lymphocyte homing/trafficking to lymphoid tissues [5,6,7,81. Suzuki and others, in in vitro studies with rat spleen cells, human peripheral blood cells, and cancer cell lines, have found that, at a serum concentration of 2 pmol/l (700 ng/ml) or more, FTY720 induces apoptotic cell death resulting in PBL reduction [9,10,11,12,13,141.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is thought to be caused by enhanced lymphocyte homing, at concentration orders of nanomoles per liter [l, 2, 3,4], via augmented expression of adhesion molecules, Gprotein-coupled chemokine receptors, and their ligands on the lymphocytes and/or high endothelial venules (HEVs) of lymph nodes (LNs) and Peyer's patches (PPs) [5,6,7,81. When FTY720 is administered at higher concentrations [i.e., at more than 2 or 4 pmol/l (700 or 1,400 ngiml)], T cells from MRL/lpr mice, rat spleen cells, human peripheral blood cells, and/or other cell lines, including cancer cells, undergo apoptosis [3, 9, 10, 11, 12, 13, 141. In experimental allogenic organ transplantation studies, FTY720 exhibited mild immunosuppression as a single-drug treatment and, when combined with conventional drugs, had synergistic immunomodulatory activity with or without adverse events [9,15,16,17,18,19,20,21,22,23,24,251.…”
Section: Introductionmentioning
confidence: 99%